Modernization the Cinema Medium through Visual Transformation of NOAH’s Album Remake Version - Teddy Afriansyah; Meyrasyawati, Dewi; Dwi Riyanto, Edi (Jurnal Seni Musik, 2025)
This research discusses how NOAH gave a modern change (modernization) sentiment in video clips, so it can be enjoyable by fans of NOAH. The objectives are, 1) Explain the visual modernization change in NOAH’s video clips remake version; and 2) Explain the visual modernization that is able to reconstruct NOAH's identity. This research uses a qualitative method with a musicological approach. The research data was collected through virtual observation from video clips of NOAH’s remake music video. This research showed that 1) a visual comparison was conducted across six NOAH music videos comparing original and remake versions, such as "Bintang di Surga," "Khayalan Tingkat Tinggi," "Yang Terdalam," "Di Atas Normal," "Menghapus Jejakmu," and "Kota Mati." The analysis identified significant transformations across five dimensions: a) technological implementation, b) visual aesthetics, c) narrative structure, d) performer roles, and e) symbolic representation. Other than, 2) the modernization elements present in NOAH's remake album successfully reconstructed the band's identity as a cross-generational act through three strategic approaches: an aesthetic transition from "organic" to "digital" paradigms, implementation of visual hybridity strategies, and symbolic reinterpretation. So, the visual modernization effectively bridges generational divides, the transformation has not been without criticism from segments of NOAH's fanbase.